Construction of a Bacillus subtilis-based expression system for Eimeria acervulina profilin - Alfredo Panebra; Youngsub Lee; Hyun S. Lillehoj (Poultry Science)
Coccidiosis is caused by apicomplexan protozoa of the genus Eimeria, which invade chicken intestinal epithelial cells, resulting in gut damage and a major poultry welfare problem worldwide. In this study, we developed a Bacillus subtilis (B. subtilis)-based vaccine delivering E. acervulina profilin (3-1E) antigen to induce protective immunity against coccidiosis in the host. A library of pBE-S-3-1E plasmid was constructed by subcloning a 3-1E open reading frame into the shuttle vector pBE-S. This library comprised approximately 900 recombinants, all expressing and secreting 3-1E, but each recombinant contained a distinct signal peptide. Following three rounds of screening using 3-1E-specific monoclonal antibodies (mAbs), 25 higher expressor recombinants were isolated and sequenced to identify the signal peptide driving 3-1E expression. From these 25 candidates, four high-expressing recombinants (#147, #241, #285-2, and #879), along with the empty vector (EV), were selected for further in vitro and in vivo assays. All recombinant clones sporulated, but clone #241 germinated at a higher rate compared to the others. Secretion of 3-1E by all germinated recombinant clones was confirmed by western blot and indirect ELISA, and further visualized by immunofluorescence assay (IFA). The conditioned media of all recombinants induced nitrite release that were neutralized by 3-1E mAb (#320) and induced significant expression of chicken IL-4, IL-6, TNF-α, IL-10 and IFN-γ (p<0.05) in HD11 macrophage cells. In vitro, phagocytosis of 3-1E recombinants by HD11 cells was significantly decreased in the following order #147> #241> #285-2> #879 compared to EV (P<0.0001). Finally, a pilot trial (N=30) was conducted to evaluate humoral and cellular immune responses in broiler chickens which were orally immunized with recombinant spores, as well as to assess spore persistence in chicken ceca in vivo. Chickens immunized with all recombinant spores exhibited significantly higher serum IgY and cecal sIgA levels to recombinant 3-1E protein compared to EV group (P<0.0001). Furthermore, splenocytes from immunized chickens demonstrated significantly increased proliferation when stimulated with recombinant 3-1E protein compared to the EV group. All colonies collected from the ceca of chickens immunized with 3-1E-recombinant spores at 10 days post-immunization were identified as positive by colony PCR.